2015
DOI: 10.5489/cuaj.2895
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the ability of multiparametric MRI to exclude significant prostate cancer prior to transperineal biopsy

Abstract: Introduction: We characterized false negative prostate magnetic resonance imaging (MRI) reporting by using histology derived from MRI-transrectal ultrasound (TRUS)-guided transperineal (MTTP) fusion biopsies.Methods: In total, 148 consecutive patients were retrospectively reviewed. Men underwent multiparametric MRI (mpMRI), reported by a consultant/attending radiologist in line with European Society of Urogenital Radiology (ESUR) standards. MTTP biopsy of the lesions was performed according to the Ginsburg rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Urologists need to be aware of the experience of the reporting radiologist when making clinical decisions based on mpMRI results. Inexperienced radiologists might overcall equivocal lesions and miss suspicious lesions, whereas experienced radiologists may help limit the number of equivocal and suspicious lesions to target with biopsies and reduce the risk of missing lesions with significant cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Urologists need to be aware of the experience of the reporting radiologist when making clinical decisions based on mpMRI results. Inexperienced radiologists might overcall equivocal lesions and miss suspicious lesions, whereas experienced radiologists may help limit the number of equivocal and suspicious lesions to target with biopsies and reduce the risk of missing lesions with significant cancer .…”
Section: Discussionmentioning
confidence: 99%
“…These patients have usually undergone previous mpMRI at their referring hospital, which is then second-read by local subspecialist uroradiologists at the tertiary centre prior to biopsy. It has previously been shown that second-opinion interpretations of mpMRI significantly improve sensitivity for extracapsular extension of prostate cancer, even after adjustment for differences in imaging techniques [ 13 ], with limited retrospective data also suggesting this may be the case for improving detection of clinically relevant lesions in false-negative mpMRIs [ 19 ]. Thus, the aim of this study was to investigate whether prospective second opinion evaluation of prostate mpMRI by subspecialist uroradiologists at a tertiary centre affects the predictive values of the report prior to transperineal fusion biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, a confirmatory repeat biopsy for any CSR on mp-MRI should be carried out by MRI or MRI/TRUS fusion image-guided target biopsy [ 27 ]. The combination of imaging-guided target biopsy and systematic TRUS biopsy may offer additional benefit particularly for those patients who did not have a prior TRUS biopsy because it can detect clinically significant tumors that are occult on mp-MRI even on retrospective evaluation due to a sparse growth pattern and a low malignant epithelium–stroma ratio [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%